Coffee marketing: what matters to coffee drinkers? / Nooraini Mohamad Sheriff ... [et al.] - Mohamad Sheriff, Nooraini; Ismail, Haslina; Abu Bakar, Zati Iwani; Damain, Danariah (Universiti Teknologi MARA, Perlis, 2016)
This study established the influence of marketing strategies on the purchase of local instant coffee. A two tier sampling approach was utilized. Simple Random Sampling was used in the first tier to select distributors of BA local instant coffee. Subsequently Judgmental sampling was exercised to select 150 consumers of local instant coffee in the Klang Valley. Self-administered questionnaires comprising of 2 sections namely demographics, marketing strategies and purchase were distributed to BA’s local instant coffee drinkers. A 5 point Likert scale was used in this study to solicit the needful responses. Data were treated to the correlation and regression analysis to establish the association and influence of marketing strategies on purchase of BA local instant coffee. It was uncovered that product strategy had the greatest influence on consumer’s purchase of BA local instant coffee. This suggests a strong need for BA Industries International to consistently safeguard the overall quality of their coffee namely taste, variety, convenient preparation, packaging, and labeling. It is also of prime importance to innovatively create sustainable differentiation through fortification of their coffee to offer health and wellness properties in the long term. Hence, there is a pressing need for BA Industries International is to engage in continuous research and innovation as a measure to contain cost and yet remain dynamic to fulfill the changing taste and preference of local coffee drinkers at par with the international coffee companies.